2017
DOI: 10.1080/03007995.2017.1297702
|View full text |Cite
|
Sign up to set email alerts
|

Comparative analysis of length of stay, hospitalization costs, opioid use, and discharge status among spine surgery patients with postoperative pain management including intravenous versus oral acetaminophen

Abstract: Background: Recovery from spine surgery is oriented toward restoring functional health outcomes while reducing resource use. Optimal pain management is a key to reaching these objectives. We compared outcomes of spine surgery patients who received standard pain management including intravenous (IV) acetaminophen (APAP) vs. oral APAP. Methods: We performed a retrospective analysis of the Premier database (January 2012 to September 2015) comparing spine surgery patients who received pain management with IV APAP … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
28
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(31 citation statements)
references
References 15 publications
2
28
0
1
Order By: Relevance
“…ERAS protocols are increasingly used following spinal fusion in patients with idiopathic scoliosis to facilitate early discharge; however, the cost efficacy of the therapeutic components used has not been studied in detail . Our results are consistent with prior research findings in adults undergoing orthopedic surgeries, where use of IV acetaminophen was found to decrease costs and lower LOS . In adults undergoing obstetric, cardiovascular, colorectal, and orthopedic surgeries, authors report decreased opioid‐related complications by 28.7% and LOS by 18.5% by the use of IV acetaminophen, with estimated cost savings of $4.5 million .…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…ERAS protocols are increasingly used following spinal fusion in patients with idiopathic scoliosis to facilitate early discharge; however, the cost efficacy of the therapeutic components used has not been studied in detail . Our results are consistent with prior research findings in adults undergoing orthopedic surgeries, where use of IV acetaminophen was found to decrease costs and lower LOS . In adults undergoing obstetric, cardiovascular, colorectal, and orthopedic surgeries, authors report decreased opioid‐related complications by 28.7% and LOS by 18.5% by the use of IV acetaminophen, with estimated cost savings of $4.5 million .…”
Section: Discussionsupporting
confidence: 86%
“…The cost impact to decreasing postoperative LOS has been suggested to be minimal . In our study, we found that costs following spine fusion in relatively healthy adolescents were mainly driven by room/board, OT/PT and pharmacy costs, as has been previously described . Observed increase in costs on POD4 was unexpected and is partly explained by 4‐fold higher costs for OT/PT on POD4 than POD3.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…The addition of acetaminophen to opioid-based postoperative pain management results in a reduction in opioid consumption of 20–40% over the first 24 hours after various major and minor surgical procedures (20)(21,22) (12,23). Whether efficacy of acetaminophen differs by route of administration is controversial; although some studies suggest benefit to IV acetaminophen (24), the majority of studies have not shown any significant benefit to the administration of IV over oral acetaminophen in decreasing opioid use (2527). There are also currently no high quality data specifically demonstrating the impact of postoperative acetaminophen on opioid consumption after reproductive/gynecologic surgery, but it is likely that the benefits observed for other surgeries will translate.…”
Section: Non-opioid Analgesicsmentioning
confidence: 99%
“…Compared with oral formulations, Intravenous paracetamol was associated with reduced length of stay, lower hospital costs and lower risk of discharge to a skilled nursing facility with a 13% less risk of 30-day readmission. 4 Evidence from another recent analysis suggests that intravenous paracetamol for prevention and treatment of newborn pain may not be the best practice. The efficacy and safety of paracetamol for the prevention or treatment of procedural and postoperative pain as well as the effects of doses and routes (enteral, intravenousor rectal) were explored for 614 infants in eight trials.…”
Section: Commentarymentioning
confidence: 99%